HUBUNGAN INTOKSIKASI ALKOHOL DENGAN BUNUH DIRI - Pangarego, Peri Desta; Situmorang , Nasib M; Sitompul, Donald F (Jurnal Kedokteran Methodist, 2022)
Background: Suicide is a serious public health problem and is currently in the global spotlight. Alcohol as a psychoactive substance can affect a person's behavior, emotions, cognition, perception, and awareness so that it becomes one of the risk factors for suicide. The purpose of this study was to determine the correlation between alcohol intoxication and suicide. Method: The method used is a literature review by analyzing related journals. The journal sources used are PubMed, Google Schoolar, and science direct. Result: Based on a literature search, 8 relevant journals were found where there is correlations between alcohol intoxication and suicide. Conclusion: Alcohol intoxication can affect suicide. The act of suicide is not only caused by one factor, many other interrelated factors can trigger suicide.